Indikator Entomologi dan Status Resistensi Jentik dan Nyamuk Aedes Aegypti Terhadap Insektisida Rumah Tangga Di Tiga Kabupaten/Kota di Provinsi Sumatera Barat - Dian Perwitasari (Jurnal Vektor Penyakit, 2019)
Abstract High data on cases of Dengue Hemorrhagic Fever (DHF) every year is the reason for continuing to monitor the breeding sites of Aedes sp., to knowing entomological indicators, and identifying the level used of resistance of insecticides The aim of the study was to observed entomological indicators, the presence of larvae in mosquito breeding sites and insecticide resistance to adult mosquitoes. This study uses a multicenter descriptive method with a cross-sectional approach. Data collection was carried out in 2015 in three districts/cities (Padang, Bukit Tinggi, and Pesisir Selatan) of West Sumatra Province. The results of the entomological indicators monitored are still in the moderate category. Mosquito breeding habitats including controllable containers with larvae positive containers so that the potential as a source of transmission is 90.27% and disposable containers which contain positive larvae of 9.94%. Insecticides used by the community, deltamethrin still showed the results of susceptible and alphacypermethrin conditions showing tolerance, whereas malathion, lamdacyhalothrin, and cypermethrin were resistant. The results of the temephos test as a larvacide used for the elimination of larvae are resistant to occur in two districts, namely Pesisir Selatan and Bukit Tinggi. Regular monitoring is needed in mosquito breeding habitats and encourages people to always care about environmental cleanliness. It is also necessary to look for alternative insecticides that are safe for the community. Abstrak Data kasus Demam Berdarah Dengue (DBD) yang tinggi setiap tahun menjadi alasan untuk terus melakukan pemantauan tempat perindukan nyamuk Aedes sp., mengetahui indikator entomologi, dan mengidentifikasi tingkat resistensi insektisida yang digunakan. Tujuan penelitian ini adalah untuk mengidentifikasi indikator entomologi, keberadaan jentik di tempat perindukan nyamuk, dan resistensi insektisida terhadap jentik maupun nyamuk dewasa. Penelitian ini menggunakan metode deskriptif dengan pendekatan potong lintang. Pengumpulan data dilakukan pada tahun 2015 di tiga kabupaten/kota (Padang, Bukit Tinggi, dan pesisir selatan) Provinsi Sumatera Barat. Hasil penelitian untuk indikator entomologi yang dipantau masih dalam kategori sedang. Habitat perkembangbiakan nyamuk yang termasuk controllable containers dengan kontainer positif jentik sehingga berpotensi sebagai sumber penularan sebesar 90,27% dan dispossable containers yang positif jentik sebesar 9,94%. Insektisida yang digunakan oleh masyarakat, deltamethrin masih menunjukkan hasil rentan dan alphacypermethrin menunjukan toleran, sedangkan malathion, lamdacyhalothrin dan cypermethrin sudah resisten. Hasil uji temephos sebagai larvasida yang digunakan untuk pengendalian jentik sudah resisten terjadi di dua kabupaten yaitu Pesisir Selatan dan Bukit Tinggi. Diperlukan pemantauan berkala di habitat perkembangbiakan nyamuk dan mendorong masyarakat untuk selalu peduli terhadap kebersihan lingkungan. Diperlukan juga mencari alternatif insektisida yang aman untuk masyarakat.